2022
DOI: 10.1177/09612033221094710
|View full text |Cite
|
Sign up to set email alerts
|

Low pre-pregnant body mass index is a risk factor for the decrease of postpartum bone mineral density in systemic lupus erythematosus patients received glucocorticoid therapy

Abstract: Objectives This study investigated postpartum bone mineral density (BMD) in patients with systemic lupus erythematosus (SLE) receiving long-term glucocorticoid (GC) therapy, assessed risk factors for decreased postpartum BMD, and evaluated change of BMD after postpartum initiation or restarting of osteoporosis drugs. Methods We retrospectively examined 30 SLE patients who gave birth and 31 non-pregnant SLE patients. In the postpartum SLE patients, BMD was measured after delivery and 1 year later. Multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Ferreira et al [61] showed that lupus is a potential contributor to PAO/LAO [61]. A retrospective study from 2022 including 30 patients with systemic lupus erythematosus in pregnancy (versus 31 non-pregnant controls suffering the same condition) confirmed postpartum BMD loss compared with controls (p = 0.048); the multivariate regression identified that low pre-conception BMI, long-term glucocorticoid exposure, and maternal age at birth were associated with hip BMD loss [88]. Furthermore, thrombophilia (factor V Leiden mutant) and anemia might contribute (single case-report level) to PAO, adding bone issues to a large panel of complications such as increased risk of gestational thrombotic events [56,93].…”
Section: Gap 4: the Playlist Of Pao/lao Contributorsmentioning
confidence: 96%
See 1 more Smart Citation
“…Ferreira et al [61] showed that lupus is a potential contributor to PAO/LAO [61]. A retrospective study from 2022 including 30 patients with systemic lupus erythematosus in pregnancy (versus 31 non-pregnant controls suffering the same condition) confirmed postpartum BMD loss compared with controls (p = 0.048); the multivariate regression identified that low pre-conception BMI, long-term glucocorticoid exposure, and maternal age at birth were associated with hip BMD loss [88]. Furthermore, thrombophilia (factor V Leiden mutant) and anemia might contribute (single case-report level) to PAO, adding bone issues to a large panel of complications such as increased risk of gestational thrombotic events [56,93].…”
Section: Gap 4: the Playlist Of Pao/lao Contributorsmentioning
confidence: 96%
“…More than 70% of females who experience the condition do not have abnormally high BMI [71]. Low pre-pregnancy BMI might induce a lower BMD after birth [88].…”
Section: Gap 4: the Playlist Of Pao/lao Contributorsmentioning
confidence: 99%